HMGB1-mediated autophagy promotes gefitinib resistance in human non-small cell lung cancer - Lei Tianyao; Huang Jiali; Xie Fei; Gu Jingyao; Cheng Zhixiang; Wang Zhaoxia (Acta Biochimica et Biophysica Sinica)
Non-small cell lung cancer (NSCLC) ranks the first in incidence and mortality among malignant tumors in China. Molecular targeted therapies such as gefitinib, an oral inhibitor of the epidermal growth factor receptor tyrosine kinase, have shown significant benefits in patients with advanced NSCLC. However, most patients have unsatisfactory outcomes due to the development of drug resistance, and there is an urgent need to better understand the pathways involved in the resistance mechanisms. In this study, we found that HMGB1 is highly expressed in drug-resistant cells and confers to gefitinib resistance in NSCLC cells via activating autophagy process. Gefitinib upregulates HMGB1 expression in time-dependent and dose-dependent manners in human NSCLC cells. RNA interference-mediated knockdown of HMGB1 reduces PC9GR cell viability, induces apoptosis, and partially restores gefitinib sensitivity. Mechanistic analyses indicate that elevated HMGB1 expression contributes to gefitinib resistance by inducing autophagy. Thus, our results suggest that HMGB1 is an autophagy regulator and plays a key role in gefitinib resistance of NSCLC.